Water for firefighting in five South African towns - Myburgh, H.M.; Jacobs, H.E. (Water S. A., 2014)
Alternative methods of firefighting and new firefighting technologies could reduce the reliance on potable water supplied via the water distribution system (WDS) for firefighting. Water required for firefighting in 5 towns in proximity to Stellenbosch, South Africa, was evaluated. The key objective of this research project was to investigate the extent to which the WDS was used for fighting fires. The fire flow requirements, specified in South African guidelines, as well as some international standards, were also reviewed. Information from fire departments in 3 municipal areas was analysed to determine the fire type category, the method for extinguishing the fire, and the water requirement to extinguish the fire. Only 8.6% of all fires were extinguished using water from the WDS by connecting firefighting equipment to a fire hydrant at the time of the fire. Most fires were extinguished by means of water ejected from a pre-filled tanker vehicle disconnected from the WDS at the time of fighting the fire. In most cases water was drawn from the WDS at a predetermined location and time, and then transported by tanker vehicle to the demand point upon receiving an emergency call. This research underlines the need for a hitherto unpublished and more realistic firefighting code for South Africa as it pertains to the WDS.